2010
DOI: 10.1021/jp107210d
|View full text |Cite
|
Sign up to set email alerts
|

On the Directed Gas Phase Synthesis of the Imidoborane Molecule (HNBH) — An Isoelectronic Molecule of Acetylene (HCCH)

Abstract: The elementary reaction of ground state boron atoms, (B((2)P(j))), with ammonia (NH(3)(X(1)A(1))) was conducted under single collision conditions at a collision energy of 20.5 ± 0.4 kJ mol(-1) in a crossed molecular beams machine. Combined with electronic structure calculations, our experimental results suggested that the reaction was initiated by a barrier-less addition of the boron atom to the nonbonding electron pair of the nitrogen atom forming a weakly bound BNH(3) collision complex. This intermediate und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…BNH 2 lies at 162.7 kJ mol −1 higher than HBNH. This value is in good agreement with the recent one of 167 kJ mol −1 , deduced by Zhang et al [1] from CCSD(T)/cc‐pVTZ calculations, and with the one of 173.0 kJ mol −1 , deduced by Rosas‐Garcia and Crawford [13] from CCSD(T) level of theory including CBS limit and core‐valence correlation corrections. Using the same methodology, they obtained that TS is situated 287.7 kJ mol −1 above the equilibrium energy of HBNH.…”
Section: Isomerization Path: Hbnh To Bnh2supporting
confidence: 91%
See 3 more Smart Citations
“…BNH 2 lies at 162.7 kJ mol −1 higher than HBNH. This value is in good agreement with the recent one of 167 kJ mol −1 , deduced by Zhang et al [1] from CCSD(T)/cc‐pVTZ calculations, and with the one of 173.0 kJ mol −1 , deduced by Rosas‐Garcia and Crawford [13] from CCSD(T) level of theory including CBS limit and core‐valence correlation corrections. Using the same methodology, they obtained that TS is situated 287.7 kJ mol −1 above the equilibrium energy of HBNH.…”
Section: Isomerization Path: Hbnh To Bnh2supporting
confidence: 91%
“…Despite its importance in chemistry, few spectroscopic studies can be found related to this molecule. The first real synthesis of imidoborane in gas phase has only been very recently reported by Zhang et al [1] by crossing a supersonic beam of boron atoms with a beam of NH 3 molecules, these compounds initially combining via a Lewis acid‐base reaction. The linear imidoborane molecule is the most stable isomer, whereas C 2v symmetric isomers (BNH 2 ) and (H 2 BN) are predicted to be higher in energy by 167 kJ mol −1 and 323 kJ mol −1 , respectively [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although structure and properties of iminoboranes have been an active field of both theoretical and experimental research for several years 4−13 only recently has the HBNH molecule been synthesized in the gas phase. 14 R−BN−R′ readily oligomerizes to stable cyclic (RBNR′) n (n = 2, 3, and 4) where substituent groups play a significant role in the factor n. 3 In these cyclization processes, HBNH changes from sp hybridization to sp 2 cyclic products, i.e, [2+2] cycloaddition to form (RBNR′) 2 . This reactivity feature raises some questions about the reaction between HBNH and boron nitride nanotubes (BNNTs) where B and N atoms are pseudo sp 2 hybridized (because of strain) and tubes contain both Lewis acid (B-sites) and Lewis base (N-sites) centers.…”
Section: Introductionmentioning
confidence: 99%